EXAMINING THE RULES OF CONSENSUS FROM THE CANONICAL PERSPECTIVE - RENTEL, Alexander (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2017)
The rules of consensus posed problems for the Holy and Great Council both prior to the council and during. This paper explores some of these reasons and examines the canonical witness for a clearer understanding of consensus within the canonical tradition. The paper concludes with a call for greater conciliar activity in order to foster a more robust culture of consensus within the Orthodox Church.